KOMPOSISI BOTANI HIJAUAN PAKAN UNTUK SAPI POTONG DI KABUPATEN REMBANG - Dwi Retno Lukiwati; Susilo Budiyanto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2010)
Improvement of forages quality and botanical composition are important to enhance beef cattle productivity. Rembang Regency is known as one of four meat production centres in Central Java Province. The objective of the research are to study the botanical composition of forages and weight gain per day of beef cattle by survey method in Rembang Regency. Data were collected through interview using structured questionnaires with 60 respondents in districts of Kragan, Pamotan, and Sumber for 6 months. Data of botanical composition were analyzed by dry weight rank method (modified) and weight gain was analyzed by Schrool method. The results showed that the botanical composition were 37, 26, 25 and 12 percent for rice stalk, sugar cane stalk, grass, and corn stalk respectively, associated with 0.19 kg/day of weight gain.